Análisis de la correlación entre la presión venosa central PVC y el índice de vena cava inferior ICCI medido ecográficamente en la evaluación del shock en los pacientes que acuden al servicio de emergencias del hospital de especialidades N° 1 de las FF.AA en Quito en el segundo cuatrimestre del 2014. - Placencia Berrú, Noela Beatriz (2015)
The index measurement of inferior vena cava and the measurement of central venous pressure are related to right ventricular hemodynamic data intrathoracic pressure and therefore should be considered taking into account the individual characteristics of patients, It is clinical shaft to guide the therapeutic decision; It is like that, in this study the relationship between the index of the Inferior vena cava was established measured by ultrasound, with measurement of central venous pressure in patients with shock Hospital Emergency Service of the Armed Forces of Quito; observational descriptive study was conducted in patients of both sexes, confirmed shock during the first quarter of 2014 diagnosis; various research tools that allowed lead to the operationalization of variables identified by criteria urgent care type of shock in each patient was determined were applied, to which underwent the determination of the inferior vena cava through ultrasonography and measurement of central venous pressure, This during admission to the emergency service, the first and second hour after the patient left the service, once it is stabilized; The following results were obtained: were attended 21 patients with septic shock, 20 with hypovolemic shock and one patient with anaphylactic shock of which: admission to emergency service 83% of patients had caval index less than 50% and central venous pressure of 6-15 mm Hg in 90% of patients; when established after treating fluid resuscitation another measure of caval index and central venous pressure is performed, yielding the following results: 98% of patients with caval index higher than 50%, while 71% remained with central venous pressures of 6 to 15 mmHg, and the remaining 29% with central venous pressures of 0-5 mmHg; noteworthy that even this instance clinical response measured by blood pressure, heart rate, respiratory rate, urinary output and O2 saturation, improved considerably, along with Cavales index measured by ultrasound. Keywords: Inferior vena cava, central venous pressure, caval index, shock, ultrasound.